Tubular injury in diabetic kidney disease: molecular mechanisms and potential therapeutic perspectives - Wang, Yu; Jin, Mingyue; Cheng, Chak Kwong; Li, Qiang (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD) is a chronic complication of diabetes and the leading cause of endstage renal disease (ESRD) worldwide. Currently, there are limited therapeutic drugs available for DKD. While previous research has primarily focused on glomerular injury, recent studies have increasingly emphasized the role of renal tubular injury in the pathogenesis of DKD. Various factors, including hyperglycemia, oxidative stress, lipid accumulation, hypoxia, inflammation, and programmed cell death, have been shown to induce renal tubular injury and contribute to the progression of DKD. Additionally, traditional hypoglycemic drugs and stem cell therapy have demonstrated their potential to alleviate renal tubular injury in DKD. This review will provide insights into the latest research on the mechanisms and treatments of renal tubular injury in DKD.